EFEKTIFITAS PENGELOLAAN ZAAT PRODUKTIF DI SEKTOR PETERNAKAN KAMBING - Maudy Rizqi Maghfirlana; Tika Widiastuti (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The purpose of this study was to find out how to optimize the management of productive zakat funds LAZ Nurul Hayat Surabaya in the goat livestock sector to achieve their desired goals. As well as the material and non-material impacts felt by mustahiq farmers from the optimization. This study uses qualitative methods with a descriptive case study strategy. The object of this research is LAZ Nurul Hayat Surabaya. By conducting in-depth interviews with 5 respondents consisting of program directors, program managers, PIC programs, and 2 assisted farmers. After interviewing the results of the study were analyzed using data triangulation to obtain conclusions. The results of this study indicate that LAZ Nurul Hayat has been optimal in managing productive zakat in the goat breeding sector. This is because LAZ Nurul Hayat in carrying out the Village Empowerment Livestock program applies three important stages, Mustahiq Screening, Production Process, and Market Potential. From this stage it can have a positive impact on mustahiq from additional income, amount of mustahiq, knowledge, to the desire to be independent.Keywords: Optimization, Management, Zakat ProductiveREFFERENCESAbdullah, Naziruddin. 2014. The effectiveness of zakat in alleviating poverty and inequalities, A measurement using a newly developed technique. Humanomics Vo. 31, No.3 : pp 314-329Adhianto, Kusuma, dkk. 2015. Analisis Ekonomi Usaha Penggemukan Kambing dengan Pakan Komplit. Prosiding Seminar Nasional Swasemabada Pangan. Politeknik Negeri Lampung.Aji, Ahmad Mukri. 2014. Optimalisasi Peran Strategis Amil Zakat dalam Perspektif Hukum Islam dan Hukum Positif Indonesia. Salam. Jurnal Filsafat dan Budaya Hukum.Akmal, Raihanul. 2018. Zakat Produktif Untuk Pengentasan Kemiskinan. Ekonomi Syariah. Fakultas Ekonomi dan Bisnis Islam. Universitas Islam Negri Ar-RaniryAli, Usman, dkk. 2012. Pembinaaan Masyarakat tani Peternak kambing dan Domba di Desa Sumbersekar, Kecamatan Dau, Kabupaten Malang. Dedikasi Vol. 9 : 60-66Almasri dan Deswimar, Devi. 2014. Peran Pemberdayaan Masyarakat Desa Dalam Pembangunan Pedesaan. Jurnal El-Riyasah Vol. 5, No. 1Al-Atsari, Abu Ihsan & E.M, M. ‘Abdul Ghoffar (Penterjemah). 2012. Tafsir Ibnu Katsir Jilid 5 & 6. Jakarta : Pustaka Imam Asy-Syafi’iAl-Ayubi, Solahuddin, dkk. 2018. Examining the Efficiency of Zakat Management : Indonesian Zakat Institutions Experiensces. . International Journal of Zakat Vol. 3(1) : p 37-55Amrullah, Haji Abdulmalik Abdulkarim.1987. Tafsir Al-Azhar jus 13-14. Jakarta : Pustaka PanjimasAtabik, Ahmad. 2015. Manajemen Pengelolaan Zakat Yang Efektif di Era Kontemporer. ZISWAF. Vol. 2, No. 1: p 57-58Aziz, Harry Azhar, dkk. 2017. Zakat & Pemberdayaan – Indonesia Zakat Development Report. Surbaya : AUP.Darmawan, Dede dan Sophia, Annisa. 2016.  Pemberdayaan Masyarakat Melalui Program ternak Domba Terpadu di Desa Karanglayung, Kecamatan Sukra, Indramayu, Jawa Barat. Jurnal CARE. Vol. 1 : 21-25Kasim, M Arif Budiman dan Siswanto, Izzuding Edi. 2014. Analisis Efektifitas Pendayagunaan Zakat produktif Pada program Pemberdayaan Masyarkat di Wilayah Sukabumi (Studi kasus : Kampoeng Ternak Dompet Dhuafa). Jurnal ekonomi dan Perbankan Syariah.Kasri, Rahmatina A. dan Putri, Niken I.S. 2018. Does Strategic Planning Matter in Enhacing Performance of Zakah Organization? Some Insight from Zakah Management in Indonesia. International Journal of Zakat Vol. 3(1) : p 1-21Muhamat, Amirul Afif, dkk. 2013. An appraisal on the business success of entrepreneurial asnaf. An empirical sudy on the state zakat organization (the Selangor Zakat board or Lembaga Zakat Selangor) in Malaysia. Journal of Financial Reporting and Accounting Vol. 11, No. 1Nurzaman, Mohamad Soleh, dkk. 2017. Evaluating of the Productive Zakat Program of BAZNAS : A Case From Western Indonesia. . International Journal of Zakat Vol. 2(1) : p 81-93Obaidullah, Mohammed. 2015. Enhacing Food security with Islamic microfinance : insights from some recent experiments. Agricultural Finance Review Vol. 75 No 2 : p 151-153Object Management Group, inc. 2011. Business Process Model and Notation Version 2.0 (Online), (http://www.omg.org/spec/BPMN/2.0), diakses 23 Januari 2019_______________________.2010. BPMN 2.0 by Example Version 1.0 (non-normative), (Online), (http://www.omg.org/spec/BPMN/2.0/examples/ZIP) diakses 23 Januari 2019Shaikh, Salman Ahmed. 2017. Role of Zakat in Sustainable Development Goals. . International Journal of Zakat Vol. 2(2) : p 1-9Sholikah, Marátus. 2017. Peran Lembaga Amil Zakat (LAZ) Dompet Dhuafa (DD) Jawa Timur Dalam Pemberdayaan ekonomi peternak Program “Ternak berdaya”di Bangkalan. Ekonomi Islam. Fakultas Ekonomi dan Bisnis. Universitas AirlanggaWidiastuti, Tika dan Mawardi, Imron. 2016. Optimalisasi Pengelolaan Dana Zakat di Lembaga Zakat Daerah : pendekatan SWOT (Strenght, Weakness, Opportunity, Threat) Analysis. Prosiding Seminar Nasional ASBIS. Politeknik Negeri BanjarmasinWidiastuti, Tika. 2015. Model Pendayagunaan Zakat Produktif Oleh Lembaga Zakat Dalam Meningkatkan Pendapatan Mustahiq. JEBIS. Vol. 1, No. 1 : p 93-94Widiyono, Irkham dan Sarmin. 2017. Pemberdayaan Peternak Marginal : Studi kasus di Wilayah Banguntapan Bantul. Indonesian Journal of Community Engagement.  Vlo. 2, No. 2 : p 170-171Yaqin, Ainol. 2015. Optimalisasi Zakat Produktif Dalam Pengentasan Problem Kemiskinan. Iqtishadia Vol. 2, No. 2Website Nurul Hayat. 2019. (Online), (http://www.nurulhayat.org, diakses pada 28 Januari 2019).Badan Pusat Statistik. 2019.Import Daging 2018. (http://www.bps.go.iddiakses 20 Februari 2019).